Increase of planar homogeneity of multi-silicon structures by gettering treatments - Litovchenko, V.G.; Efremov, A.A.; Evtukh, A.A.; Rassamakin, Yu.V.; Klyui, M.I.; Kostylov, V.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Two types of gettering treatments are considered and compared from the viewpoint of their usefulness to decrease LD scatter over the wafer in multi-silicon photovoltaic structures. It was found that in both cases high degree of homogeneity in LD distribution over the sample surface and cleaning of the samples from recombination active impurities are achieved. Possible mechanisms of the homogenization are briefly discussed.